Synthesis of 1-Benzyl-4-[2-(5-phenyl-1,3,4-thiadiazole-2-yl)aminoethyl]piperidine as Potential Alzheimer’s Disease Modifying Agent - Nabardi Sarkandi, Diba; Firoozpour, Loghman; Asadipour, Ali; Sheibani, Vahid; Alizadeh Monavar Asli, Mahsa; Davood, Asghar; Shafiee, Abbas; Foroumadi, Alireza (Asian Journal of Chemistry, 2011)
A number of pharmacological agents are available for clinical use in the treatment of alzheimer's disease. The cognitive impairment associated with alzheimer's disease is characterized by reduced levels of acetylcholine in CNS. Acetyl cholinesterase inhibitors increase the level of acetyl choline at the synapses by blocking the breakdown of the neurotransmitter. The aim of this study is the synthesis of 1-benzyl-4-[2-(5-phenyl-1,3,4-thiadiazole-2-yl)aminoethyl]piperidine, as potential acetyl cholinesterase inhibitor, from the reaction of 2-chloro-5-phenyl-1,3,4- thiadiazole and 1-benzyl(piperidin-4-yl)ethylamine. The structure of obtained compound was identified by its 1H NMR, mass and IR spectra